Efficacy of continuous neuromonitoring in thyroid surgery: preliminary report of a single-center experience - Lombardi, Celestino Pio; Waure, Chiara De; Mariani, Marco; Carnassale, Giulia; D’Amore, Annamaria; Traini, Emanuela; Crea, Carmela De; Raffaelli, Marco (Gland Surgery, 2019)
Background: The continuous intraoperative nerve monitoring (CIONM) technique seems to be acknowledged as a useful tool to prevent impending nerve injury, because it constantly provides valuable real-time information. Aim of the study is to evaluate the impact of the CIONM technique on functional outcome i.e., recurrent laryngeal nerve (RLN) palsy, compared to the traditional surgical procedure. Methods: From January to December 2016, 197 patients who underwent thyroid surgery were included in this retrospective study: 94 patients had CIONM procedure and 103 traditional technique, according to the order of the operating room list. Results: A total of 8 patients showed a damage to left or right vocal cord: 3 patients after CIONM procedure, and 5 patients after traditional surgical procedure. After matching for propensity score, 188 patients were eventually considered and 7 RLN palsy were identified: 3 in CIONM and 4 in traditional surgical procedure. The analysis performed on the matched propensity score sample showed a non-significant difference between the two procedures. Conclusions: In our experience no significant differences in functional outcomes were found between the use of CIONM and the standard technique.